The Development Strategy of Halal Tourism Industry in Malaysia - Febri Wulandari (Universitas Pendidikan Indonesia, 2024)
Halal tourism is considered one of the most profitable markets and markets in the tourism industry. Malaysian tourism ranks first in the world's Muslim travel records. Malaysia is one of the ASEAN countries and is assessed to benefit from the use of tourist tourism. This article discusses the development strategy of Malaysia's tourism industry. This study uses a qualitative descriptive approach in data collection and uses content analysis techniques. The research results show that the barrier to the development of halal tourism is that the staff is not yet prepared and there are still many places that do not comply with the regulations of the tourism industry. The solution to this problem is through a joint strategy of power management among stakeholders through policy formulation, implementation and promotion, brand building calculations, communication strategies and approval. Current development includes site access, office development and support areas. Thirdly, there are trainings, entrepreneurs, industrial planners and workshop organization.